Methodological add-ons to a non-destructive, micro-CT-based taxonomic/morphometric analysis of characean remains - Benyó-Korcsmáros, Réka; Gulyás, Sándor; Sebők, Dániel; Benyó, Dániel; Cseh, Péter; Sümegi, Pál (Geologos, 2023)
Ever since its introduction, computed tomography has come a long way. No longer is it merely a method that is used in clinical diagnostics, but it is becoming more and more popular among palaeontologists because it can be used to analyse both external and internal structures of fossil remains, such as small insects, snail shells and plant remains. The present study describes non-destructive analyses of Late Cretaceous and early Holocene charophyte gyrogonites by using the micro-CT technique, from sample preparation (embedding, fixing) to visualisation and assessment of images obtained. In addition to this non-destructive examination, we wished to test whether or not computed tomography could be used to examine the gyrogonites. Our preliminary results have made it clear that the micro-CT technique is worth employing for further research. It has proved possible to visualise the samples in 3D, rotate them, and observe them from different directions. By using the appropriate parameters, we have also been able to observe density differences between parts of characean remains and to study several important defining features of these.